Sustainable Marketing: A Marketing Revolution or A Research Fad - Kortam, Wael; Mahrous, Abeer A. (Archives of Business Research, 2020)
This paper aims to demonstrate that while marketing and sustainability might seem to be as different as "A Polar Bear and A Bengal Tiger", there is growing evidence that the two disciplines have something to offer each other and the universe. With a view toward gaining this synergy, this research proposes that a lasting sustainability marketing as an academic discipline and managerial practice must aim deliberately and thoroughly to reassure itself as an outstanding potential for a marketing revolution and distance itself away from the danger of ending up as a quick-shot research fad. Conclusively, a sustainability marketing revolution can be sparkled and kept alive and a sustainability marketing research fad can be avoided and reversed through a number of highly recommended visible venues of marketing research and managerial pursuits.